A multimodal reading of public protests. (September 2019) - Day, Sarah; Seedat, Mohamed; Cornell, Josephine; Suffla, Shahnaaz
Public protests in (un)democratic polities, reflective of discursive articulations of resistance and material expressions of struggle, seek to disrupt prevailing unjust societal, political and cultural practices. The insurrectionist purposes of protests are often in contravention of public order regimens, which seek to regulate enactments of public protests, minimise the disruptions inherent to protests and legitimise those defined as non-violent. This produces a non-violent–violent protest binary, which fails to account for the dynamic nature of protests. This study, critical of the non-violent–violent binary, assumed a multimodal analysis of unedited video footage of a selected authorised protest in the City of Cape Town, South Africa to understand the rapid discursive and kinaesthetic shifts that may occur within single protest events. The findings suggest that protests shift between moments of resistance and insurgency and moments of appeasement of official scripts. As such, protest enactments within a particular discursive space seem to be constitutive of resistance to power, insurgence and cooperation as well as actions defined either as legitimate or illegitimate by official discourse.